Gender Representation in the English Textbook “When English Rings A Bell” - Hesti Miranda (Jurnal Perempuan dan Anak, 2019)
Therevisedbook“WhenEnglishRingsABell” (2014)isastandardized textbookof2013CurriculumfromtheMinistryofEducationandCulture which isrecommendedforteacherstouseinmostofjuniorhighschools inIndonesia. Given thatEnglishiscompulsory subjectin theschoolbegininjuniorhighschoolgrade seven,teachersshouldbeawareof thecontentof theEnglishtextbook.This studyfocusedonthegenderrepresentationintheEnglishtextbook:“When EnglishRingsA Bell”written by Siti Wachidahusedinjuniorhigh school.The purposeofthisstudyisto analyzegenderrepresentationintheEnglishTextbook.Following Stockdale’ssuggestion,therewere threeaspectsthattheresearcheranalyzed, namely thenumbersoffemaleandmale,illustration,andnounandpronoun. In accordance to that, this research wasmixmethod; quantitative andqualitative. The aspects beingresearchedwereanalysedquantitatively,whilethematerial interpretationwasanalyzedqualitatively.Theaspectswillbepresentedinnumber.The resultshowedthatfemalerepresentationdominatedintwo aspectsincludingthe numbersoffemale/male,andnounandpronoun.While,malewereonlyrepresented inillustration. Therefore,theresearcher concludedthatthereisunequal gender representation inthe“When English Rings A Bell”.